Numerical Optimization and Experimental Validation of Finite Perforated Cellular Panels for Vibration Reduction - Saavedra-Flores, E (Multidisciplinary Digital Publishing Institute (MDPI), 2025)
Mechanical vibrations in lightweight structures remain a persistent challenge, often leading to noise, fatigue, and performance degradation in aerospace, automotive, and industrial applications. Recent advances in phononic crystals and perforated metaplates have shown that periodic cavities or uniformly distributed perforations can generate bandgaps and reduce vibration transmission. However, most existing designs rely on identical and regularly spaced holes, which limits the ability to precisely tune the attenuation response. This work introduces a novel design and optimization framework for finite perforated cellular panels, in which each perforation diameter is individually optimized to achieve targeted vibration suppression within specific frequency ranges. Finite element models were coupled with a Particle Swarm Optimization (PSO) algorithm to minimize the frequency response function (FRF) amplitude. Aluminum panels with 16 and 25 perforations were optimized, fabricated via CNC machining, and experimentally validated using impact hammer tests. The optimized designs achieved up to 90% reduction in vibrational amplitude within the target frequency bands, demonstrating strong agreement between numerical predictions and experimental results. These results highlight the potential of non-periodic, locally optimized perforation patterns as a practical and scalable approach for vibration control in finite structural components. © 2025 by the authors.